Analysis of Religious Behavior of Street Vendors in Percut Sei Tuan District - Anwar, Khairil; Rubino, Rubino (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Religious behavior is a person’s awareness of carrying out religious activities. Religious behavior is a pattern of beliefs that can be seen from a person’s habits, namely in the form of his physical, spiritual, emotional, and social abilities. Religious behavior is also referred to as a form of a person’s awareness of the existence of God which is manifested by understanding religious values, obeying all God’s commands, and avoiding his prohibitions in order to be safe in this world and the hereafter. This research aims to analyze the religious behavior of street vendors. The method used in this research is a qualitative method. Data collection in this research was obtained through observation and interviews. The results of this research are that street vendors, with their busy lives, namely selling, do not become an obstacle for them. These street vendors continue to carry out Allah’s orders, carry out their worldly obligations by trading but do not forget their obligations in the afterlife. Street vendors continue to carry out their obligatory worship in accordance with Allah’s commands. The implication of this research is by analyzing street vendors, it is known that street vendors continue to carry out God’s commands and have religious behavior that can be an example for other traders so that they continue to carry out God’s commands even though they are busy and have busy daily activities.